Effectiveness of Educational Modules on Knowledge on Brucellosis among Dairy Farmers in Northern India - Verma, Arjun Prasad; Meena, Hans Ram; Patel, Diksha; Meena, B. S. (Indian Journal of Extension Education, 2021)
The study was carried out to assess the effectiveness of an educational module on brucellosis among commercial dairy farmers. Experimental research design before and afterÂ was used to test the effectiveness of the Educational module. A total of 120 commercial dairy farmers were selected and interviewed using a well-structured interview schedule from six districts of Haryana and Punjab States during 2018. The results revealed that theÂ majority of the respondents (55%) had not heard about brucellosis and didnâ€™t know causative agent of brucellosis (55%). The majority of the respondents mentioned that theyÂ did not know the symptoms of brucellosis, mode of transmission, method of prevention and vaccine used for brucellosis in dairy animals. Before exposure to the educational module,Â the percentage of knowledge was 12.03 per cent and after exposure 46.54 per cent. Mean knowledge gain was 34.51 per cent. Knowledge gain through educational module onÂ brucellosis in dairy animals was positively and significantly correlated with education, landholding, income, herd size and experience in commercial dairy farming.